Detection and examination in a forgotten bill of Criminal Code (Academic Journal of Internal Affairs, 2021)
The first act of comprehensive codification of both criminal law and criminal procedure in Hungary was the bill of Criminal Code in 1795. In the same time, the establishing of the first Criminal Code was also in progress in Transylvania. That was the bill of Criminal Code in 1811 which has not been published in Hungary or elsewhere in Hungarian so far. Considering the history of Hungary and Transylvania and comparing these two bills, we can see that they have their common roots. The Transylvanian bill of Criminal Code has a strong relation to the Hungarian legal traditions while it also has his Transylvanian legal characteristics. Furthermore, elements and affection of the old feudal law and that of the Enlightenment live together in both of the bills. On occasion of the 210th anniversary of the Transylvanian bill, it may be interesting to talk about its provisions. In this essay I analyse its provisions concerning extrajudicial procedural acts before the impeachment, the acts of investigation so to say. According to the bill, the first stage of investigation is the detection consisting of the provisions concerning indicia, denunciations and general examination. In the second stage we find the (extrajudicial) examination of suspects and preliminary examination. Further provisions concerning investigation, like those of the investigation of witnesses, can be found among the rules of judicial examination and probation. After analysing all these provisions of the Transylvanian bill of Criminal Code we can see that the acts of investigation are basically levelled at the examination and recognition of individuals and objects nowadays and also in the era of the first codifications. If we draw off the acts of investigation brought by the technical development of the previous two centuries, we mostly find the same acts of investigation today which were applied in the late 18th and the early 19th centuries. Finally, all these recognitions make it interesting to recall the forgotten elements of our legal history.
Keywords: Transylvania; 1811; Criminal Code; detection